Temperature Effect on Stability of Tunnel Face Under Unsaturated Seepage Condition - Yi Xie; Hong Liao; De Zhou (Applied Sciences)
As tunnel excavation technology matures and the demand for transportation infrastructure continues to grow, several high-temperature tunnels have successively emerged in high geothermal areas. The construction of tunnels in high-temperature regions is gradually becoming a new challenge encountered in the engineering field. This study aims to conduct a stability analysis of tunnel face excavation under different temperatures. In addition, soil is often considered to be unsaturated. A framework for assessing the stability of tunnel faces in unsaturated soils under fluctuating temperature conditions is proposed, with an analytical approach. The theoretical basis of this framework is established on the influence of temperature on the shear strength of unsaturated soil. The matric suction of unsaturated soil changes with temperature, thereby inducing variations in shear strength. The temperature-induced variation in apparent cohesion is quantified utilizing a temperature-sensitive effective stress model coupled with a soil–water characteristic curve. These models are subsequently incorporated into the stability assessment of tunnel faces in unsaturated soils under steady-state flow conditions. A three-dimensional logarithmic spiral model is utilized to ascertain the unsupported pressure on tunnel faces, with the safety factor (FS) being calculated through an iterative methodology. Subsequently, a comprehensive suite of parametric studies is undertaken to explore the influence of temperature on tunnel face stability under unsaturated seepage conditions, offering valuable insights for practical engineering endeavors.